Pengaruh Pendidikan Kewirausahaan, Adversity Intelligence, dan Kreativitas Terhadap Minat Berwirausaha Mahasiswa Fakultas Ekonomika dan Bisnis UNESA - Putra, Andika Permana; Sakti, Norida Canda (Universitas Pendidikan Ganesha, 2023)
Study This aims to determine the effect of entrepreneurship education, adversity intelligence, and creativity towards entrepreneurship interests of Unesa Faculty of Economics and Business students. The sample in this study were 239 students from 8 study programs Class of 2019. The data analysis technique used in this research is the Multiple Linear Regression analysis technique usingsoftware IBM SPSS Statistics version 24. The results of this study indicate that the variable entrepreneurship education has a significant effect on interest in entrepreneurship, adverisity intelligence has a significant effect on interest in entrepreneurship, creativity has a significant effect on interest in entrepreneurship and the three variables simultaneously influence interest in entrepreneurship for FEB Unesa students class of 2019. In the t test, it was found that the calculated t value generated on the entrepreneurship education variable was 4.068 with a sig of 0.000. Means that individually the variable of entrepreneurship education has a significant effect on the interest in entrepreneurship variable. The calculated t value is generated on the variableadversity intelligence ( is 3,301 with a sig of 0.001. It means that individually variable adversity intelligence significant effect on the interest in entrepreneurship variable. The calculated t value generated on the creativity variable is 6.934 with a sig of 0.000. Means that individually the creativity variable has a significant effect on the interest in entrepreneurship variable. value on the regression model of 0.713 (71.3%) can be interpreted that the ability of the regression model variable entrepreneurship education, adversity intelligence, and creativity explains the variable interest in entrepreneurship (Y) of 71.3% and the remaining 28.7% is influenced by other independent variables.